FORMS AND METHODS OF THE COUNTRY STUDY MATERIALS' USED AT THE ENGLISH LESSONS (American Journal of Pedagogical and Educational Research, 2023)
Various forms and methods of work with the country study material at the English lessons are considered in this article. In the opinion of this article author, when conducting English lessons, the following should be used: texts oriented to country studies though language, authentic letters, and proverbs, idiomatic expressions. The above listed forms of introducing the materials on country study and country studies through language have a beneficial effect on the foreign culture understanding by students and facilitate in their involvement in dialogue between cultures and develop the general learning skills of students.